Studi Fenomenologi Pola Asuh Anak oleh Wanita Indonesia dalam Perkawinan Campur di Eropa dan Kanada - Ruslaini Ruslaini; Tanti Sugiharti; Diajeng Herika Hermanu; Wahyu Wulandari; Sahala Harahap (PERSPEKTIF, 2021)
This research aims to find out how the parenting pattern is conducted by Indonesian women who experience mixed marriage where they marry foreign men and live in their husbands’ countries. The research method used is Qualitative with Phenomenological approach.  Using Purposive Sampling Technique, five Indonesian women were gathered as informants where 3 of them live in Europe :  The United Kingdom, The Netherlands and Germany while 2 others live in Canada. Data collection was conducted using online questionnaire and semi-structured interviews to be further analysed using Interpretative Phenomenological Analysis (IPA)  to reveal in detail how participants interpreted their personal and social worlds. The results show that participants conduct Democratic parenting style; a combination of  appreciation for the individuality of the children and  efforts to shape social values gradually. This parenting pattern was formed by building an agreement with their husbands towards  their own religions and Indonesian cultures. The country provision and protection of children aged 18 to have the rights to live separately from their parents has encouraged participants to conduct some particular standards for their children. Additionally, the results  show that participants managed to conduct similar parenting style held by their parents.